Mortality in acute stroke: predictive value of lipid profile and routine investigations - Pandey, Prakash Chandra; Dwivedi, Naresh Chandra; Yadav, Rakesh Kumar; Sonkar, Kamlesh Kumar (International Journal of Advances in Medicine, 2017)
Background: The prognostic value of routine blood investigations in acute stroke has not been adequately studied. Most studies do not use accumulative measurement of these parameters and numbers of subjects taken were less. In this study we assess the impact of these simple parameters on the mortality in acute stroke patients as well as their correlation with clinical findings. Methods: Total 205 consecutive patients of acute stroke presented within 72 hours of symptom onset were studied. After clinical evaluation and neuroimaging, routine blood investigations along with lipid profile estimations were performed. The patients were followed up for a maximum period of 30 days from onset of stroke. Results: After analysis it was demonstrated that out of all clinical parameters low Glasgow Coma Scale (GCS), higher systolic and diastolic blood pressure can strongly predict fatality significantly. Among blood investigations raised leukocyte counts(TLC) , erythrocyte sedimentation rate, blood urea, serum creatinine, serum bilirubin along with decreased level of total cholesterol (p=0.0001) and low density lipoprotein (LDL) (p=0.02) signifies their accumulative importance in predicting fatality in expired patients. But after logistic regression analysis only GCS, TLC, blood urea, serum creatinine and total cholesterol independently correlate with mortality. Conclusions: Our study shows that it is useful to take necessary interventions, accordingly in early hours focusing on correctable parameters in acute stroke to prevent mortality in acute stroke.